STRATEGI PEMERINTAH DAERAH KABUPATEN BREBES DALAM UPAYA MEMPEROLEH OPINI WAJAR TANPA PENGECUALIAN (WTP) ATAS LAPORAN KEUANGAN PEMERINTAH DAERAH (LKPD) - Alvianita Gunawan Putri; Ardian Widiarto; Musyafa Al Farizi (Faculty of Economic and Business Universitas STIKUBANK, 2021)
The purpose of this research is to analyze the efforts of the Pemerintah Daerah Kabupaten Brebes to obtain an Unqualified Opinion (WTP) on the Government Financial Report (LKPD). This study uses a qualitative approach with descriptive methods. This study used a SWOT analysis and data collection was carried out by in-depth interviews and was supported by observation, documentation and triangulation. Based on the processed data, it can be concluded that in the strength factor, the highest average is the commitment and high integrity of the Pemerintah Daerah Kabupaten Brebes and the Board of Institution Leaders, with a value of 7.9. The lowest average value is on the weakness factor, the area of Brebes Regency so that the total assets are larger and more complex, with a value of 6.0. The highest average value is on the opportunity factor in (Bimtek) and socialization from the central government with a value of 7.7. The lowest average value on the threat factor (Threat), the culture of the community that does not consider education is important, with a value of 6.1. The SO strategy gets the highest score of 4.17, so it can be said that the SO strategy are the best alternative. Keywords: Opinion, Regional Government Financial Statements, Unqualified Opinion (WTP)